2021
DOI: 10.1186/s40478-021-01287-3
|View full text |Cite
|
Sign up to set email alerts
|

RyR1-related myopathy mutations in ATP and calcium binding sites impair channel regulation

Abstract: The type 1 ryanodine receptor (RyR1) is an intracellular calcium (Ca2+) release channel on the sarcoplasmic/endoplasmic reticulum that is required for skeletal muscle contraction. RyR1 channel activity is modulated by ligands, including the activators Ca2+ and ATP. Patients with inherited mutations in RyR1 may exhibit muscle weakness as part of a heterogeneous, complex disorder known as RYR1-related myopathy (RYR1-RM) or more recently termed RYR1-related disorders (RYR1-RD). Guided by high-resolution structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…The first mode represents the initiation of activation, where the adenine group of ATP formed a hydrogen bond with H4983 and the ribose formed a hydrogen bond with T4979 in the closed state without strong interactions with the S6c segment. Mutation T4979 results in the failure of this binding mode of ATP . After RyR1 activates, inducing a structural rearrangement in the ATP binding site, ATP switches to the second binding mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first mode represents the initiation of activation, where the adenine group of ATP formed a hydrogen bond with H4983 and the ribose formed a hydrogen bond with T4979 in the closed state without strong interactions with the S6c segment. Mutation T4979 results in the failure of this binding mode of ATP . After RyR1 activates, inducing a structural rearrangement in the ATP binding site, ATP switches to the second binding mode.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation T4979 results in the failure of this binding mode of ATP. 56 After RyR1 activates, inducing a structural rearrangement in the ATP binding site, ATP switches to the second binding mode. In this mode, ATP maintains an open conformation, enabling adenine to switch its interaction to the hydrophobic cleft, and ribose changes the location of hydrogen bonding to M4954, preserving the direction of the S6c segment in the open state.…”
Section: Resultsmentioning
confidence: 99%
“…RYR1 loss-of-function mutations result in reduction of Ca 2+ release due to either an impairment of RYR1 and DHPR functional coupling, through the so called “uncoupling” mechanism ( Avila et al, 2001 ; Avila et al, 2003 ), or a reduced channel opening resulting from alterations in sites of interaction with endogenous activators ( Yuan et al, 2021 ). The majority of uncoupling mutations are localized in the C-terminal region of the channel containing the pore domain, within the 4895 GGGIGDE 4901 amino acid sequence in humans ( Gillespie et al, 2014 ).…”
Section: Loss-of-function Mutations In Ryr1: In Vitro Characterizatio...mentioning
confidence: 99%
“…Indeed, the RYR1 mutation T4980M, associated with a recessive form of congenital myopathy with cores, is located within the RYR1 ATP-binding site ( Klein et al, 2011 ; Maggi et al, 2013 ). Functional studies showed that this mutation results in reduced channel activation, which may explain the muscle weakness observed in humans ( Yuan et al, 2021 ). Similarly, the Q3969K mutation, linked to a form of CCD, is located close to the Ca 2+ binding site of RYR1 and results in a reduction in Ca 2+ -dependent channel activation ( Yuan et al, 2021 ).…”
Section: Loss-of-function Mutations In Ryr1: In Vitro Characterizatio...mentioning
confidence: 99%
See 1 more Smart Citation